Kesejahteraan dan Keadilan Ekonomi : Studi Tentang Kebijakan Ekonomi Khalifah Harun Ar-Rasyid (786-809 M) - Nur Fitri Eka Asbarini; Abdul Chalel Rahman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Caliph Harun ar-Rasyid was a successful ruler in his leadership. He made significant efforts to advance Islamic civilization, particularly in the economic sphere, which flourished under his rule. The achievements during his reign left a profound impression on his people. The aim of this research is to examine the economic policies implemented by Harun al-Rasyid concerning welfare and economic justice during his time. This study is a library research, involving the collection of data sources such as books, documents, and historical records about Harun ar-Rasyid. The findings indicate that Harun ar-Rasyid successfully elevated the popularity of the Abbasid dynasty and the Islamic world to its zenith through improvements in the welfare of his people and economic justice, as evidenced by his various contributions to the economy, society, and politics.